The effect of intravenous immunoglobulins on the outcomes of patients with COVID-19: a systematic review and meta-analysis of randomized controlled trials. Issue 10 (3rd October 2022) - Lai, Chih-Cheng; Chen, Wang-Chun; Chen, Ching-Yi; Wei, Yu-Feng
ABSTRACT: Objectives: Severe-to-critical COVID-19 has been associated with exaggerated immune responses, and anti-inflammatory agents including corticosteroid and interleukin-6 antagonist have been repurposed as the treatment modality against severe SARS-CoV-2 infections. However, the clinical efficacy and safety of intravenous immunoglobulin (IVIG) in the treatment of patients with COVID-19 was controversial. Methods: This meta-analysis of randomized controlled trials (RCTs) investigated the effectiveness of IVIG in patients with COVID-19. Electronic databases were searched for RCTs that compared the clinical efficacy of IVIG with standard of care or placebo in the hospitalized patients with COVID-19 were included. Results: Six RCTs involving 472 patients were included. Patients who received IVIG had a similar mortality rate to the controls (25.3% vs 27.0%, odds ratio [OR], 0.60; 95% confidence interval [CI], 0.27–1.31). Compared with the control group, the study group demonstrated a similar incidence of receiving mechanical ventilation (OR, 0.70; 95% CI, 0.45–1.11), intensive care unit (ICU) admission (OR, 0.58; 95% CI, 0.22–1.53), length of hospital stay (mean difference [MD], −1.81 days; 95% CI, −8.42 to 4.81) and ICU stay (MD, −0.61 days; 95% CI, −2.80 to 1.58). Conclusions: The administration of IVIG in hospitalized patients with COVID-19 does not improve clinical outcomes.